2017
DOI: 10.3892/ol.2017.7135
|View full text |Cite
|
Sign up to set email alerts
|

Potential factors influencing the development of oral tongue squamous cell carcinoma in young mature patients: Lingual position of the mandibular second molar and narrow tongue space

Abstract: The lingual position of the mandibular second molar and narrow tongue space are associated with oral tongue squamous cell carcinoma (OTSCC) development in young mature patients. The present study aimed to assess the role of the mandibular second molar position and tongue space in young mature patients with OTSCC. The medical records of 21 patients with OTSCC aged <50 years, who had an intact mandibular second molar and had undergone computed tomography (CT) imaging between April 2009 and December 2015 at the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…[12,[26][27][28][29][30][31][32] However, since the duration of the exposure to the aforementioned causes is apparently shorter in AYA patients than in elderly patients, those causes cannot be applied for the development of OTSCC in AYA patients. Kim et al [33] reported that the lingual position of the mandibular second molar and the narrow tongue space in young mature patients are associated with tongue cancer development. Therefore, we believe that AYA patients with OTSCC tend to have specific anatomical physical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…[12,[26][27][28][29][30][31][32] However, since the duration of the exposure to the aforementioned causes is apparently shorter in AYA patients than in elderly patients, those causes cannot be applied for the development of OTSCC in AYA patients. Kim et al [33] reported that the lingual position of the mandibular second molar and the narrow tongue space in young mature patients are associated with tongue cancer development. Therefore, we believe that AYA patients with OTSCC tend to have specific anatomical physical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of OSCC are diagnosed at a late phase, in stages III or IV, which markedly decreases the chances of survival and leads to a significant deterioration in patient quality of life. Despite the currently available therapeutic strategies, which include the excision of malignant tissue in combination with radiotherapy and chemotherapy, the 5‑yr survival rate is still around 50% [6] , [7] , [8] . In addition, a high percentage of patients have a poor response to therapy and high recurrence rates.…”
Section: Introductionmentioning
confidence: 99%